Is Homeworking a Better Option in the Digital Era? An Empirical Research across EU Member States - Predeţeanu-Dragne, Daniela; Tudor , Ion; Popescu, Dan; Nicolae, Valentina (European Journal of Sustainable Development, 2020)
The complex and also very dynamic progress of information and communication technologies (ICT) enabled workforce to become more increasingly mobile. By consequence, the companies across the world have already adapted their work arrangements, offering more and more flexibility to their employees, to name just a few examples: homeworking, outsourcing, crowdsourcing, part-time work, temporary work, flexible working time. Our scientific approach represents an in-depth analysis of the homeworking trend within the EU Member States, by factors such as country and gender. It also examines the way ICT have evolved in enterprises across all Member States and provides specific trends per country. Furthermore, the research presents a comparative study of how the ICT skills enabled by companies has evolved over the last years and improved employee’s lives. The results of our approach show that work from home trends increased in all EU Member States in parallel with the development of digital skills. This development make the companies to be more competitive on the market in attracting and retaining employees. In practice, companies will be required to diversify their work programs and allow flexibility in terms of working schedules and actual location of work. Of course, at the same time, the management of each company must pay a special attention to develop the ICT skills, so that people are properly equipped to perform efficiently and ensuring that the organizational performance is maintained at highest standards. Keywords: flexible workplace, work from home, information and communication technologies